2007
DOI: 10.3758/bf03193305
|View full text |Cite
|
Sign up to set email alerts
|

The negative cascade of incongruent generative study-test processing in memory and metacomprehension

Abstract: Can students evaluate their understanding of cause-and-effect relations? The effects of diagram completion on monitoring accuracy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
55
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(60 citation statements)
references
References 44 publications
5
55
0
Order By: Relevance
“…appropriate processing (TAP) theory, for example, purports that memory performance depends on how well the encoding operations match with those required at test, and processes associated with active retrieval under the testing context better match with processes in the final retrieval than do those associated with restudying (Morris, Bransford, & Franks, 1977;Roediger & Karpicke, 2006b;Thomas & McDaniel, 2007). However, as pointed out by Karpicke and colleagues (2014), the largest effects of retrieval practice are found after free recall or short test formats rather than after tests that match the final test.…”
mentioning
confidence: 99%
“…appropriate processing (TAP) theory, for example, purports that memory performance depends on how well the encoding operations match with those required at test, and processes associated with active retrieval under the testing context better match with processes in the final retrieval than do those associated with restudying (Morris, Bransford, & Franks, 1977;Roediger & Karpicke, 2006b;Thomas & McDaniel, 2007). However, as pointed out by Karpicke and colleagues (2014), the largest effects of retrieval practice are found after free recall or short test formats rather than after tests that match the final test.…”
mentioning
confidence: 99%
“…Concept map construction is an intervention specifically targeting the situation model. Thiede, Wiley and Griffin (2011) showed that providing instructions about what kind of test to expect and giving practice tests focused college students on appropriate cues and produced more accurate monitoring (see also Thomas & McDaniel, 2007). Two additional advantages arise from assessing the validity of concept map construction as an intervention with a youner population.…”
mentioning
confidence: 99%
“…Another approach that has been taken toward improving metacomprehension accuracy has been to align judgments and tests by manipulating encoding activities (e.g., Griffin, Wiley, & Thiede, 2008;Thomas & McDaniel, 2007). For instance, Thiede, Griffin, Wiley, and Anderson (2010) had college students construct concept maps, which focused participants on the connections of ideas among the texts while reading.…”
mentioning
confidence: 99%